Biochar amendment of a metal contaminated soil partially immobilized Zn, Pb, and Cd and reduced ryegrass uptake - Antonangelo, Joao Arthur; Zhang, Hailin; Sitienei, Isaac (Frontiers in Environmental Science, 2023)
Soil heavy metals (HM) contamination threatens soil and water quality, which significantly affects humans and animals. This study focuses on the competitive immobilization of zinc (Zn), lead (Pb), and cadmium (Cd) in soils from a contaminated site using ryegrass (Lolium perenne) in a potting experiment amended with biochars. Increased rates of switchgrass- (SGB) and poultry litter-derived biochars (PLB) were applied before ryegrass cultivation. Soil HM phytoavailability and HM concentrations in plant shoots were determined. Multivariate regression models were used to evaluate the influence of several soil chemical attributes on the HM phytoavailability. The increased rates of both biochars reduced the Zn, Pb, and Cd availability (p<.001). Langmuir models showed that the maximum HM immobilization (IMAX) was 169.2±29.5 mg kg–1 for Zn with SGB, and 20±7.4 (Pb) and 1.08 mg kg–1 (Cd) with PLB. The extended Langmuir model (EL) showed competitive HM immobilization since there was a decrease in the IMAX of Zn (∼90±28 mg kg–1 from SGB) and Cd (∼0.70±0.21 mg kg–1). Negative values of Pb and Cd immobilization at low rates of SGB indicated an increase in those HM availabilities and preferential immobilization for Zn. The reduced Zn and Pb uptake in ryegrass shoots ranged from 70–98% and were optimum at rates of 0.50±0.00–0.60±0.06% for both biochars, and 1.6±0.4% of SGB for Cd. The stepwise multiple linear regression (SMLR) and partial least squares (PLS) revealed that pH and organic matter (OM) were the most responsible factors for reducing Zn bioavailability while OM was more impactful in decreasing Pb and Cd levels. This suggests that the preferential immobilization for Zn relies on its higher sensitivity to the pH increase. Also, the ubiquitous positive relationship among the metals studied shows that competitive immobilization is ceased at high rates of biochars application. Path analysis (PA) showed that pH and OM were the common contributors from both biochars to simultaneously affect Zn, Pb, and Cd availability regardless of the contrasting physicochemical properties of the two bioproducts. This work proved the potential of applying low rates of two contrasting feedstock-derived biochars to remediate the contaminants and safely grow ryegrass.